Long-term exposure to BAY2416964 reduces proliferation, migration and recapitulates transcriptional changes induced by AHR loss in PyMT-induced mammary tumor cells - Olafsen, Ninni Elise; Das, Siddhartha; Gorrini, Chiara; Matthews, Jason (Frontiers in Oncology, 2024)
The aryl hydrocarbon receptor (AHR) is a ligand activated transcription factor which in certain cancer types drives pro-survival processes that facilitate tumorigenesis, malignant cell migration, invasion, and metastasis. Much of AHR’s pro-tumorigenic action is due to its activation by the oncometabolite, kynurenine. Because of this AHR antagonists are being actively investigated as new anti-tumor therapy. In this study we compared the effects of treatment with the AHR antagonists, BAY2416964 and GNF351, to that of AHR knockout in PyMT murine mammary cancer cells. BAY2416964 and GNF351 effectively inhibited kynurenine-dependent increases in Cyp1a1 and Cyp1b1 mRNA levels. CRISPR/Cas9-generated PyMT AhrKO cells exhibited reduced cell proliferation compared with controls, but treatment with 1 μM BAY2416964 for 96 h had no effect on the proliferation of wildtype cells. To further examine the differences between AHR knockout and short term BAY2416964, we generated long-term BAY2416964 (LT-BAY) cells by exposing wildtype cells to 1 μM BAY2416964 for at least 6 weeks. Similar to AhrKO cells, LT-BAY cells exhibited reduced cell proliferation and migration compared with wildtype cells. No differentially expressed genes (DEGs) were identified in wildtype cells exposed to 1 μM BAY2416964 for 24 h; however, 46.4% of DEGs overlapped between AhrKO and LT-BAY cells including gene regulated cell proliferation. Our data reveal long-term pharmacological inhibition of AHR by BAY2416964 closely resembles AHR loss in a mouse model of breast cancer.